PERANAN SEKTOR INFORMAL DALAM PENYERAPAN TENAGA KERJA DAN PENINGKATAN PENDAPATAN NELAYAN DI WILAYAH PANTAI PASIR PUTIH SITUBONDO - Bambang Suyadi (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2016)
Mount earnings of fisherman as family head of generally relative lower, others sum up responsibility of big family asa result the requirement live one day the cannot be fullfiled better, this condition push member of family of fisherman to follow to work aseffort add domestic earnings. Type of Workwhich familier done in informal sector that is exploit marine product to be processed further more,therefore research of about role of informal sector in absorb of labour and improvement earnings of done important domestic.Target of this research is to : (1) knowing type and character of laboured informal sector;(2)knowing influence factor of cause of decision work [in] informal sector to labour absorbtion;(3)knowing the level of contribution of informal sector to domestic earnings. This research is conducted in region of white sands of Situbondo. Determination of Responder of research with method of proporsional random sampling. Sum upsampel from member of family of fisherman of equal to 59 Responder from population a number of 144. To reply target of used byfirst research of descriptive analysis, target of research of second use equation of doubled linear regresi and target of third third research--use-analysis prosentase. The result of research show type of effort elaborated by member of family of fisherman is make diligence from cookle ; making fishing nets;labouring pemindangan fish;and labour fish draining. There is influence which significant from decision cause factor work in informal sector(sumupfamily responsibility,mount fisherman earnings, mount education, and old age) to labour absorption ofeither through simultan and also byparsial. Level of informal sector contribution mean to domestic earningsis 54,3 procent to make diligence cockle; 50,4 procent for pemindangan fish ;21,8 procentfor the making net fish,and 37,6 procent for the fish draining. From various the effurt type of making of diligence of cockle give biggest contribution to domestic earning sand lowest is making net fish. Pursuantto result of research is hence recommended in order to various type of informal sector laboured by member of family of fisherman given by construction by on duty Industry and Commerce of Situbondo is and also given ready of cheap credit by related/relevantinstitute in frame improve level live fisherman society, with consideration of various type of the effort can improve economic growth namely : (1)to the number of opportunity work by family of fisherman with appearance of is effort domnestic and (2) can improve addedvalue so that give contribution to domestic earnings.